دلالة توظيف الرمز في الرواية الجزائرية الحديثة - أصابع لوليتا لواسيني الأعرج أنموذجا - مروة, عمرة; مسعود, وقاد (جامعة الوادي - University of Eloued, 2021)
استطاعت الرواية الجزائرية الحديثة أن تحقق ثراء فنيا متميزا، لا سيما خلال الفترة الأخيرة من القرن العشرين، ومطلع القرن الراهن حيث تمكنت على يد جيل تواق وطموح للتجديد أن تبرز مكانتها فعرفت انتشارا كبيرا في الساحة الأدبية، كونها تعالج القضايا الاجتماعية بطريقة فكرية ونفسية، فهي تمثل أهم الفنون والأجناس الأدبية خاصة في مجالات الفنون السردية كافة، وهي التي احتوت العديد من المميزات والخصائص والظواهر والتحولات، فكان الرّمز من الظواهر الفنية التي لجأت إليها، فهو يعد أهم وسيلة يستخدمها الروائيون في بلوغ الإتقان الفني، والقدرة على التوصيل والتأثير وكذلك لتطوير اللغة والسموّ بها وتقديم أرقى اللوحات الفنية التي تعبر عن أعماق الوجدان البشري، فقد استفاد الروائيون من إعادة النظر في التراث القديم ليجعلوا منه مصدرا للرمز في قصائدهم، وبما أن الرمز يلعب دورا فعالا في إثراء التجربة الروائية . فقد جاء بحثنا ليقف على هذه التجربة في رواية أصابع لوليتا لواسيني الأعرج، محاولين الإجابة عن بعض الأسئلة منها : ما الرّمز ؟ و ماهي أنواعه؟ وما دلالة الرموز التي استخدمها الروائي واسيني الأعرج في روايته المخصوص بالدراسة والتحليل؟ The modern Algerian novel managed to achieve a distinct artistic richness, particularly during the last period of the twentieth century and the beginning of the current century. Hence it was able, by anexcitedand ambitious generation for renew alto highlight its position and spread widely in the literary field, as it addresses social issues in an intellectual and psychological way. The most significant arts and literary genres, especially in all fields of narrative arts, which contained many features, characteristics, phenomena and transformations, so the symbol was one of the artistic phenomena that I resorted to, as it is the most important tool used by novelists to gain artistic perfection, the ability to communicate and influence, as well as to develop language and transcend it and to introduce the finest artistic paintings that express the depths of the human conscience. Therefore, the novelists have benefited from a review of the ancient heritage to make it a source of symbolism in their poems, and since the symbol plays an effective role in enriching the narrative experience. Our research aims to stand on this experience in the novel “the Fingers of Lolita” by Waciny Laredj, attempting to answer some questions, including: What is the symbol? What are its types? What is the significance of the symbols used by the novelist Waciny Laredj in his novel for study and analysis?
مقال
Keywords: لسرد ; الرواية ; الرمز ; أنواع الرمز ; دلالة الرمز; narration ; symbol ; symbol types ; symbol indication ; the novel